A Co-Culturing Approach Enables Discovery and Biosynthesis of a Bioactive Indole Alkaloid Metabolite - Fleurdeliz Maglangit; Qing Fang; Kwaku Kyeremeh; Jeremy M. Sternberg; Rainer Ebel; Hai Deng (Molecules, 2020)
Whole-genome sequence data of the genus Streptomyces have shown a far greater chemical diversity of metabolites than what have been discovered under typical laboratory fermentation conditions. In our previous natural product discovery efforts on Streptomyces sp. MA37, a bacterium isolated from the rhizosphere soil sample in Legon, Ghana, we discovered a handful of specialised metabolites from this talented strain. However, analysis of the draft genome of MA37 suggested that most of the encoded biosynthetic gene clusters (BGCs) remained cryptic or silent, and only a small fraction of BGCs for the production of specialised metabolites were expressed when cultured in our laboratory conditions. In order to induce the expression of the seemingly silent BGCs, we have carried out a co-culture experiment by growing the MA37 strain with the Gram-negative bacterium Pseudomonas sp. in a co-culture chamber that allows co-fermentation of two microorganisms with no direct contact but allows exchange of nutrients, metabolites, and other chemical cues. This co-culture approach led to the upregulation of several metabolites that were not previously observed in the monocultures of each strain. Moreover, the co-culture induced the expression of the cryptic indole alkaloid BGC in MA37 and led to the characterization of the known indolocarbazole alkaloid, BE-13793C 1. Neither bacterium produced compound 1 when cultured alone. The structure of 1 was elucidated by Nuclear Magnetic Resonance (NMR), mass spectrometry analyses and comparison of experimental with literature data. A putative biosynthetic pathway of 1 was proposed. Furthermore, BE-13793C 1 showed strong anti-proliferative activity against HT-29 (ATCC HTB-38) cells but no toxic effect to normal lung (ATCC CCL-171) cells. To the best of our knowledge, this is the first report for the activity of 1 against HT-29. No significant antimicrobial and anti-trypanosomal activities for 1 were observed. This research provides a solid foundation for the fact that a co-culture approach paves the way for increasing the chemical diversity of strain MA37. Further characterization of other upregulated metabolites in this strain is currently ongoing in our laboratory.